Decorative explosion-proof membrane with liquid crystal colors
By applying high adhesion hardened coating and liquid crystal coating on the PET substrate of the decorative film of the mobile phone back cover, combined with the adhesive layer, a self-propelled liquid crystal color explosion-proof film with a colorful effect is solved, and the existing decorative film is solved. The problems of color fading and de-inking under ultraviolet and infrared irradiation have achieved high adhesion and three-dimensional decorative effects, meeting the needs of the high-end market.
Patent Information
- Application Number
- CN202411607657.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The decorative film of the existing mobile phone back cover is prone to fading and de-inking under ultraviolet and infrared rays, and lacks a three-dimensional layering and color fluidity, which cannot meet the high-end market's demand for beauty and texture.
An explosion-proof film with its own liquid crystal color is used to form a decorative film with a colorful effect by applying a hardened coating and a liquid crystal coating with high adhesion on the PET substrate.
It has achieved the bright colors and high adhesion under high temperature and humidity conditions, increased the aesthetics and uniqueness of the decorative film, met the high-end market's demand for three-dimensionality and color conversion, and at the same time reduced production costs and equipment demand.
Smart Images

Figure CN119463721A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass and panel decoration, in particular to a self-contained liquid crystal color decorative explosion-proof film. Background Art
[0002] With the development of technology, the appearance design of electronic products such as mobile phones and tablets has attracted more and more attention from consumers. Among them, the decorative effect of the back cover of the mobile phone is particularly important. Due to the application of 4G and 5G, the back cover of the mobile phone cannot be made of metal materials, and most of them use tempered glass. At this time, a printable explosion-proof film is indispensable, which can not only play an explosion-proof protection role, but also improve the overall appearance of the mobile phone. At present, there are two main ways to decorate the back cover of mobile phones on the market:
[0003] Publication No.: CN209987496U The pattern is directly printed or sprayed on the surface of PMMA or PC, and then hot-pressed to form the shape of the back cover of the mobile phone.
[0004] Publication No.: CN209428447U A decorative film for a mobile phone glass back cover. The provided mobile phone glass back cover decorative film has the characteristics of easy printing, multiple colors, good peeling resistance, temperature change resistance, moisture resistance and heat resistance.
[0005] Publication No.: CN110527448A A decorative film is processed on the reverse side of the substrate layer 1 as needed, a nanoimprint layer 22 is made on the lower base coating layer 21 by nanoimprint technology, and then a niobium oxide layer, a silicon oxide layer, an indium layer, and a silicon oxide layer are sputtered or evaporated on the nanoimprint layer 22 in sequence by magnetron sputtering technology to form a coating layer 23. The resulting decorative film has a more textured feel and richer color and reflective visual effects.
[0006] Publication number: CN209987496U, due to the lack of glass texture and brightness, plus the lack of vividness of the printed colors, it can only be used in some low-end mobile phones or repair markets. The high-end panels or mobile phone back covers in the market are still mainly made of glass.
[0007] Publication number: CN209428447U, CN110527448A is a decorative film invention, the dyne value of which reaches 42Dyn / cm, and can be easily processed by UV glue transfer, PVD electroplating and ink printing. After the decorative film is attached to the transparent glass,
[0008] It solves the problem that ion diffusion, chemical plating, and vacuum plating cannot be performed on the curved surface of the glass back cover. At the same time, the color of the decorative film can be selected according to needs. However, it has the following disadvantages:
[0009] 1. The printing ink will lose color and de-ink over time under the irradiation of ultraviolet and infrared rays.
[0010] 2. This technology has the problem that the colors and patterns lack three-dimensional layers and color fluidity, and it can no longer meet people's current aesthetic requirements.
[0011] Among them, the third type, CN110527448A, uses nanoimprint technology to make a nanoimprint layer on the other side of the substrate, and then uses magnetron sputtering technology to sputter or evaporate metal layers of multiple elements on the nanoimprint layer in turn to form a decorative film. With the subsequent printing processing, it has a more textured feel, and the color and reflective visual effects are richer. Although this invention increases the color texture, it also has the following shortcomings:
[0012] 1. Due to the multi-layer sputtering of multiple elements of metal, although the texture and reflective feeling of the color are improved, the transparency is not enough, the color of the later processing cannot be well reflected, and the sense of flow color, three-dimensional layering and color conversion is also missing.
[0013] This invention needs to add nano-imprinting and magnetron sputtering in the processing, and the equipment is quite expensive, and the equipment is imported from abroad, the element metal is also very expensive, and the production yield and efficiency are low. The production cost is very high and the market is difficult to accept. Summary of the invention
[0014] The purpose of the present invention is to provide a self-contained liquid crystal color decorative explosion-proof film, which solves the problems raised in the above-mentioned background technology.
[0015] Technical Solution
[0016] To achieve the above purpose, the present invention is implemented by the following technical scheme: a self-contained liquid crystal color decorative explosion-proof film, including a hardened coating, the hardened coating containing 15%-25% toluene solvent, 18%-22% ethyl ester solvent, 16%-20% ketone solvent, 32%-45% acrylate prepolymer, 20%-35% acrylate monomer, 12%-25% polymethyl methacrylate particles, 0.5%-3% photoinitiator (184 and TPO), and 0.1%-1% auxiliary agent. Preparation method: the acrylate monomer and the solvent are mixed evenly, and then the photoinitiator is added, and after stirring evenly, a hardened coating liquid with high hardness, abrasion resistance and high adhesion is obtained. Usage: evenly apply the above hardening coating liquid on the surface of the substrate, the dry coating thickness is 0.3-3um, then dry the solvent in an oven, and then cure it by ultraviolet light to form a hardened layer with high surface hardness and high adhesion. At the same time, a protective film is compounded on the hardened primer surface, and rolled up to make a PET with a high hardness primer with a protective film;
[0017] The colored liquid crystal coating comprises 50%-65% of solvent-based nano-scale cholesteric liquid crystal, 20%-25% of cyclohexanone, 15%-20% of cyclopentanone, 0.1%-0.5% of anti-settling agent, and 0.1%-0.5% of leveling agent. Preparation method: the cholesteric liquid crystal, cyclohexanone, cyclopentanone, anti-settling agent, and leveling agent are mixed and stirred evenly;
[0018] Usage: 1. Apply the stirred liquid crystal liquid evenly on the untreated PET surface, and dry it in an oven. At this time, the liquid crystal molecules will automatically arrange and stack as the solvent evaporates to form a thin film state, which will gently adhere to the PET and be rolled up to make a peelable and transferable liquid crystal coating.
[0019] 2. Take high-viscosity adhesive, add solvent ethyl ester and stir evenly, evenly apply it on the non-priming surface of the PET with high hardness primer, and after curing in an oven, stick it to the liquid crystal surface of the prepared liquid crystal coating. Using the strong double-sided adhesion of the adhesive, the liquid crystal coating and the non-priming surface of the PET with high hardness primer are tightly bonded together, and rolled into a film with a liquid crystal layer on one side and a high hardness adhesion on the other side.
[0020] By mixing the above ingredients in a certain proportion, a fast heat dissipating adhesive can be obtained. Among them, the amount of thermal conductive material added should be properly controlled to ensure the bonding performance and operability of the adhesive.
[0021] The two-component acrylic high-viscosity adhesive is prepared by dispersion polymerization of the following materials in the following proportions using a high-pressure reactor: component A: methyl methacrylate 45-60, hydroxyethyl methacrylate 20-30, ABS (solid) 25-35, epoxy resin 8-12, and reinforcing agent 0.2-1.
[0022] Component B: methyl methacrylate 110-160, hydroxyethyl methacrylate 25-55, nitrile rubber (solid) 20-30, reducing agent amine 2-6, methyl ene acid 12-25. Dispersant 1-2 active diluent 6-10, leveling agent 1-4, defoamer 0.5-2, solvent: ethyl acetate 1-5%, tert-butyl alcohol 5-15%, butyl acetate 30-40%, acetylacetone 5-15%, ethylene glycol dicyanoacrylate 3-8, divinylbenzene 5-10, dianhydride 0.5-1, silane 0.6-1, PR25, 4-methoxybenzylidene dimethyl malonate 1-3
[0023] An improvement of the present invention is to add a high temperature resistant and water resistant stable polymer material to the above acrylic adhesive, 3-8 ethylene glycol dicyanoacrylate, 5-10 divinylbenzene, 0.5-1 dianhydride, 0.6-1 silane and the above acrylic resin and other materials to disperse and polymerize them in a high pressure reactor.
[0024] Ensure that the adhesive will not lose adhesion, loosen or warp at high temperatures.
[0025] Usage: Add the synthesized component A and component B into the mixing tank at a ratio of 100:1.2, and stir for 30 minutes. Evenly apply it on the surface of the liquid crystal coated in the previous process (tear off the PET layer on the original liquid crystal surface before coating), and stick the release film at the same time to make a finished decorative explosion-proof film with its own liquid crystal color layer.
[0026] The present invention provides a self-contained liquid crystal color decorative explosion-proof film, which has the following beneficial effects:
[0027] This self-contained liquid crystal color decorative explosion-proof film uses optical grade PET, PC, PVC, TPU and other materials as the base material, and applies a high adhesion coating on the surface of the base material. The adhesion of this coating to PET can reach 5B, and the polarity of its coating surface is high, which has excellent adhesion to ink, UV transfer glue, electroplating, etc., effectively solving the problem that the coating of the decorative film is easy to fall off and fade after aging test or long-term use when printing. A liquid crystal silver brightening layer is made on the other side of the base material to increase the appearance of the subsequent printing pattern, so that when the customer prints the pattern on the other side, it will present a sense of hierarchy and three-dimensionality, and it will increase the brightness of the pattern, effectively solving the problem that the decorative film has a single color tone and no hierarchy and three-dimensionality when printing the pattern. It completely replaces the magnetron sputtering process, saves equipment costs, raw material costs, and labor manufacturing costs, and applies a layer of adhesive with low initial viscosity, high lasting viscosity, heat resistance, fast heat dissipation, and super cohesive force on the liquid crystal silver high-reflection brightening layer. The low initial viscosity has good bubble removal and reworkability, so that when the printed film is bonded to the glass, the efficiency is increased by 30%, and it is easy to rework. There is no residual glue when the adhesive layer is torn off, the material reuse rate is high, and the loss of material is reduced. It effectively solves the problem that the decorative film cannot be bonded to glass with large curved shapes, such as 2.5D and 3D mobile phone back covers. Liquid crystal is used as the coating, and the structural light wave color formed by the free arrangement of liquid crystal molecules on PET is used, so that when viewed from different angles, the colors presented are different, with a colorful effect, which increases the beauty and uniqueness of the decorative film. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the present invention. DETAILED DESCRIPTION
[0029] like Figure 1 As shown, the embodiment of the present invention provides a self-contained liquid crystal color decorative explosion-proof film, including a specific embodiment: divided into four major processes,
[0030] Process 1: making a surface hardening primer layer.
[0031] Process 2: making liquid crystal coating.
[0032] Process three: bonding the liquid crystal coating.
[0033] Process 4: Apply adhesive layer.
[0034] Implement process 1 to make a surface hardened base coating:
[0035] Step 1: 15%-25% toluene solvent, 18%-22% ethyl ester solvent, 16%-20% ketone solvent, 32%-45% acrylate prepolymer, 20%-35% acrylate monomer, 12%-25% polymethyl methacrylate particles, 0.5%-3% photoinitiator (184 and TPO), 0.1%-1% additive. Add to the reactor, the working pressure of the reactor is 0.25MPa, the working temperature is 60-75℃, and the stirring reaction time is 4 hours. After the reaction is completed, when the test viscosity is 1500-3000, stop stirring, let it stand at room temperature, and then pour it out to obtain a hard and high-adhesion primer liquid A.
[0036] Step 2: Use the coating machine to apply the prepared coating liquid A evenly on the surface of the substrate of the above structure ③ (the substrate can be PET.PC.PVC, TPU.TPH.), and the coating thickness is 0.1-5um. After baking at 80℃ for 1 minute, cure it with 1500gm UV light for 3 seconds. At this time, the coating has been dried and cured, and the surface is flat and non-sticky. At the same time, a protective film is attached to the surface of the coating ②, and then rolled into a large roll. At this time, a film with high hardness and adhesion is obtained (process one) ①-③ in the structure diagram.
[0037] Process 2: Making liquid crystal coating:
[0038] Step 1: Add 50%-65% of solvent-based nano-scale cholesteric liquid crystal, 20%-25% of cyclohexanone, 15%-20% of cyclopentanone, 0.1%-0.5% of anti-settling agent, and 0.1%-0.5% of leveling agent into a reactor with a working pressure of 0.25MPa, a working temperature of 50-60℃, and a stirring reaction time of 4 hours. After the reaction is completed, when the viscosity is 500-1000, stop stirring, let it stand at room temperature, and pour it out to obtain a coating liquid A with liquid crystal.
[0039] Step 2: Apply the stirred liquid crystal liquid A evenly on the untreated PET surface, with a coating thickness of 0.1-5um. Bake in an oven at 110℃ for 2 minutes and dry. At this time, the liquid crystal molecules will automatically stack and form a thin film state as the solvent evaporates, gently adhere to the PET, and roll up to form a peelable and transferable liquid crystal coating (structure diagram ⑤ layer).
[0040] Process 3: Bonding the LCD coating:
[0041] Step 1: Take a high-viscosity adhesive, add solvent ethyl ester and stir evenly, evenly apply it on the non-priming surface of the PET with high hardness primer, and after curing in an oven, stick it to the liquid crystal surface of the prepared liquid crystal coating. Using the strong double-sided adhesion of the adhesive, the liquid crystal coating and the non-priming surface of the PET with high hardness primer are tightly bonded together, and rolled into a film with a liquid crystal layer on one side and a high hardness adhesion on the other side (①-⑤ layers).
[0042] Process 4: Apply adhesive layer:
[0043] Step 1: Add 45-60% methyl methacrylate, 20-30% hydroxyethyl methacrylate, 25-35% ABS (solid) into the adhesive preparation reactor, the temperature in the reactor is 72-85℃, the pressure in the reactor is controlled between 0.1 and 0.25MPa, and the stirring time is continued for 3-4 hours. After the materials are completely dissolved, cool down, add 8-12% epoxy resin and 0.2-1% reinforcing agent. Keep the temperature in the reactor at 70-85℃, the pressure in the reactor is controlled between 0.1 and 0.25MPa, and the stirring time is continued for 3-4 hours. After the materials are completely dissolved, cool down, test the viscosity between 10000 and 20000, and pour out to obtain adhesive A.
[0044] Step 2:
[0045] In the rubber preparation reactor, add 110-160% methyl methacrylate, 25-55% hydroxyethyl methacrylate, 20-30% nitrile rubber (solid), and 5-15% acetylacetone. The temperature in the reactor is 70-85℃, the pressure in the reactor is controlled between 0.1 and 0.25MPa, and the stirring time is continued for 6-8 hours. After the materials are completely dissolved, cool down and the test viscosity is 15000-25000. Add reducing agent amine 2-6, methyl ene acid 12-25, dispersant 1-2, active diluent 6-10, leveling agent 1-4, defoamer 0.5-2, solvent: ethyl acetate 1-5%, tert-butanol 5-15%, butyl acetate 30-40%, ethylene glycol dicyanoacrylate 3-8, divinylbenzene 5-10, dianhydride 0.5-1, silane 0.6-1, 4-methoxybenzylidene dimethyl malonate 1-3 and continue stirring for 10-12 hours. After the material is completely dissolved, cool it down and test the viscosity to be 15000-25000 to obtain adhesive B.
[0046] Step 3:
[0047] Pour the above-prepared adhesives A and B into the glue preparation tank at a ratio of (A) 0.2-0.6: (B) 100, stir for 30 minutes, let stand to defoam, and then evenly apply them on the surface of the liquid crystal layer (process three) with a liquid crystal layer on one side and a film with high hardness and adhesion (①-⑤ layers) on the other side using a comma scraper or slit coating method of a coating machine, with a coating layer thickness of 25-50um. Bake in an oven at 120℃ for 2 minutes, attach the isolation layer film, and roll it up.
[0048] At this time, the invention obtains a liquid crystal color decoration explosion-proof film with dazzling colors, and at the same time realizes a riot-proof film with high hardness and wear resistance, high adhesion, high heat insulation and fast heat dissipation.
Claims
1. A self-contained liquid crystal color decorative explosion-proof film, including a hardened coating, characterized in that: The hardening layer coating contains 15%-25% toluene solvent, 18%-22% ethyl ester solvent, 16%-20% ketone solvent, 32%-45% acrylate prepolymer, 20%-35% acrylate monomer, 12%-25% polymethyl methacrylate particles, 0.5%-3% photoinitiator (184 and TPO), and 0.1%-1% auxiliary agent. Preparation method: Mix the acrylate monomer and solvent evenly, then add the photoinitiator, and stir evenly to obtain a hardening coating liquid with high hardness, abrasion resistance, and high adhesion. Usage method: Apply the above-mentioned hardening coating liquid evenly on the surface of the substrate, the dry coating thickness is 0.3-3um, then dry the solvent in an oven, and then cure it by ultraviolet light to form a hardening layer with high surface hardness and high adhesion. At the same time, a protective film is compounded on the hardened primer surface, and rolled up to make a PET with a high hardness primer with a protective film; The colored liquid crystal coating comprises 50%-65% of solvent-based nano-scale cholesteric liquid crystal, 20%-25% of cyclohexanone, 15%-20% of cyclopentanone, 0.1%-0.5% of anti-settling agent, and 0.1%-0.5% of leveling agent. Preparation method: the cholesteric liquid crystal, cyclohexanone, cyclopentanone, anti-settling agent, and leveling agent are mixed and stirred evenly; Usage:
1. Apply the stirred liquid crystal liquid evenly on the untreated PET surface, and dry it in an oven. At this time, the liquid crystal molecules will automatically arrange and stack as the solvent evaporates to form a thin film state, which will gently adhere to the PET and be rolled up to make a peelable and transferable liquid crystal coating.
2. Take high-viscosity adhesive, add solvent ethyl ester and stir evenly, evenly apply it on the non-priming surface of the PET with high hardness primer, and after curing in an oven, stick it to the liquid crystal surface of the prepared liquid crystal coating. Using the strong double-sided adhesion of the adhesive, the liquid crystal coating and the non-priming surface of the PET with high hardness primer are tightly bonded together, and rolled into a film with a liquid crystal layer on one side and a high hardness adhesion on the other side. By mixing the above ingredients in a certain proportion, a fast heat dissipation adhesive can be prepared. The amount of thermal conductive material added should be properly controlled to ensure the bonding performance and operability of the adhesive. The two-component acrylic high-viscosity adhesive is prepared by dispersion polymerization of the following materials in the following proportions using a high-pressure reactor: component A: methyl methacrylate 45-60, hydroxyethyl methacrylate 20-30, ABS (solid) 25-35, epoxy resin 8-12, and reinforcing agent 0.2-1. Component B: methyl methacrylate 110-160, hydroxyethyl methacrylate 25-55, nitrile rubber (solid) 20-30, reducing agent amine 2-6, methyl ene acid 12-25. Dispersant 1-2 active diluent 6-10, leveling agent 1-4, defoamer 0.5-2, solvent: ethyl acetate 1-5%, tert-butyl alcohol 5-15%, butyl acetate 30-40%, acetylacetone 5-15%, ethylene glycol dicyanoacrylate 3-8, divinylbenzene 5-10, dianhydride 0.5-1, silane 0.6-1, PR25, 4-methoxybenzylidene dimethyl malonate 1-3 An improvement of the present invention is to add a high temperature resistant and water resistant stable polymer material to the above acrylic adhesive, 3-8 ethylene glycol dicyanoacrylate, 5-10 divinylbenzene, 0.5-1 dianhydride, 0.6-1 silane and the above acrylic resin and other materials to disperse and polymerize them in a high pressure reactor. Ensure that the adhesive will not lose adhesion, loosen or warp at high temperatures. Usage: Add the synthesized component A and component B into the mixing tank at a ratio of 100:1.2, and stir for 30 minutes. Evenly apply it on the surface of the liquid crystal coated in the previous process (tear off the PET layer on the original liquid crystal surface before coating), and stick the release film at the same time to make a finished decorative explosion-proof film with its own liquid crystal color layer.
Citation Information
Patent Citations
Decorative film
CN110527448A
Decorative film for mobile phone glass back cover
CN209428447U
Novel mobile phone rear cover
CN209987496U